Escritura feminina e desgarrada - Doval, Camila Canali (2012)
This dissertation consists of a theoretical essay and a work of fictional creation. The theoretical essay's main objective is to discuss the hypothesis of a female writing as it appears in the form of textual marks. The discussion starts with questions about authorship and references in the written language, as it has been discussed since Saussure up to the feminist criticism. The intention is not to draw a timeline between them, but concatenate thoughts that support the concreteness of difference. The work of creation results in a fictional novel built from the author's experience as a woman and nourished by the theory that have accompanied its construction.